Vaccines against human papillomavirus to prevent cervical cancer - Castellsagué, Xavier (2015)
Virus-like particles have been synthetized from a self-assembling L1 protein, using celular and bacterial expresion systems. Human papillomavirus (HPV) virus-like particle prophylactic vaccines are effective in preventing infection and lesions caused by the targeted HPV type. Clinical trials with 3 vaccine prototypes (HPV16, other with HPV 16/18 and other with 6/11/16/18) have demonstrated their safety, immunogenicity and efficacy to prevent CIN 2/3, immediate precursors of invasive cervical carcinoma. Vaccination programs with adequate coverage would have the potential to substantially reduce morbidity and mortality related to cervical cancer. This paper presents data from clinical trials of the above mentioned vaccines.